To what degree and through which channel do central banks other than the Federal Reserve cause spillovers? - Christopher D. Cotton (Federal Reserve Bank of Boston, 2023)
Spillovers play a crucial role in driving monetary policy around the world. The literature focuses predominantly on spillovers from the Federal Reserve. Less attention has been paid to spillovers from other central banks. I measure the degree to which 20 central banks cause spillovers. I show that central banks in medium- to high-income countries cause spillovers to medium- to long-term interest rates in similar countries through a bond-pricing channel. These effects are narrower than spillovers from the Federal Reserve, which also affect emerging markets, short-term interest rates, and other assets. However, they are still pronounced. Fourteen central banks other than the Federal Reserve cause significant spillovers: the central banks of Australia, Canada, Czechia, the eurozone, Japan, Mexico, Norway, New Zealand, Poland, Romania, South Korea, Sweden, Switzerland, and the United Kingdom. Consequently, the Federal Reserve causes only one-fifth of the spillovers to 10-year interest rates, and the United States is the recipient of large spillovers. My results imply that central banks, especially the Federal Reserve, are affected by greater spillovers than is commonly believed, and that non-Fed central banks cause spillovers through a bond-pricing channel.
Keywords: F42; E43; E52; 330; monetary policy spillovers; central bank; global financial cycle